Streamlining the formation of virtual enterprises in the aerospace industry - Farr, Richard; Buxton, David; Bovik, Catarina; MacCarthy, Bart L. (2006)
The virtual enterprise is an ideal solution to the pace of change in modern markets, where increasingly well-informed customers demand high performance, customised products, with continuing downward pressure on prices and lead times. In meeting customer requirements of this kind, the level of investment demanded of an individual manufacturer may be prohibitive, but success can be achieved through collaboration between businesses.